(untitled) (Nigerian Journal of Technology, 2018)
The study investigated the influence of information literacy skills on the use of e-library resources in tertiary institutions in Akwa Ibom State. Students need information for a variety of activities and the e-library is a resource center for providing a wide range of electronic resources that can meet any academic purpose. However, the use of electronic resources is largely dependent on the skills and information literacy of the students. An empirical survey was carried out to examine the impact of computer literacy skills among undergraduate students in tertiary institutions in Akwa Ibom state on the use of e-library resources. A total of 500 questionnaires were administered and analyzed using ANOVA. The study reveal that the quality and volume of academic work is largely influenced by the knowledge and skills possessed in the use of e-library resources. It therefore concluded that students in tertiary institutions need to update their information literacy skills. http://dx.doi.org/10.4314/njt.v37i2.17